Women, faith, and culture - Longgeita Pinem, Milda (Bogoslovni vestnik, 2025)
This article explores the critical role of inculturation theology in advancing women’s empowerment within various cultural and religious frameworks, with a focus on achieving gender equality and breaking down the barriers erected by patriarchal and misogynistic norms. A thorough review of the literature traces the development of inculturation theology within Christianity, highlighting its flexibility and applicability across different cultures, as demonstrated by case studies in Zambia and the Philippines. It addresses the persistent challenges women encounter due to deep rooted social conventions, and shows how the fusion of Christian principles with cultural traditions serves as a powerful means for confronting these challenges. This article underscores the theology’s potential to drive societal transformation, champion gender equality, and amplify women’s presence in both religious and wider societal spheres. It stresses the importance of the continued application of inculturation theology to create fairer and more inclusive spaces for women worldwide, calling for further research and application in this field.
Keywords: Christianity; culture; empowerment; inculturation theology; krepitev vloge; krščanstvo; kultura; marginalizacija; marginalization; teologija inkulturacije; women; ženske